(untitled) (Colombia Medica, 2021)
Damage control surgery is based on temporal control of the injury, physiologic recovery and posterior deferred definitive management. This strategy began in the 1980s and became a formal concept in 1993. It has proven to be a strategy that reduces mortality in severely injured trauma patients. Nevertheless, the concept of damage control in non-traumatic abdominal pathology remains controversial. This article aims to gather historical experiences in damage control surgery performed in non-traumatic abdominal emergency pathology patients and present a novel management algorithm. This strategy could be a surgical option to treat hemodynamically unstable patients in catastrophic scenarios such as hemorrhagic and septic shock caused by peritonitis, pancreatitis, acute mesenteric ischemia, among others. Therefore, damage control surgery is light amid better short- and long-term results.